Writer to writer : from think to ink - Levine, Gail Carson (Harper, an imprint of HarperCollins Publishers, 2015)
"In this lively nonfiction book for young readers, bestselling author Gail Carson Levine shares her secrets of great writing"--Provided by publisher.